Predictive Value of Cellular Immune Response and Tumor Biomarkers in Patients Surgically Treated for Cervical Cancer in Relation to Clinical Outcomes" - Ancuta, E.; Ancuta, Codrina; Sofroni, D. (IntechOpen, 2012)
None